KEDUDUKAN MANUSIA DI DUNIA DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - ., Nuryamin (Inspiratif Pendidikan, 2018)
Talking about humans and their position, means placing humans and everything that has to do with them, both potential and actual. In other words, humans are given advantages by God compared to other creatures. The advantages are both in physical form, and in the spiritual structure. Physical structures consisting of several five senses can be useful in receiving knowledge and becoming knowledge called empirical knowledge. Positivism is also born of empirical knowledge. Pancaindera consists of the eyes, ears, nose, skin and taste buds also possessed by other beings, but cannot capture knowledge through its senses, only humans can capture empirical knowledge. While the spiritual structure is even more amazing, because it has the power of spiritual power, heart power, reasoning and life force. Humans have the power to carry out their functions, both as di abdi (mu’abbid), khalifah fi al-ardh, as well as immarah fi al-ardh. As Mu’abbid, humans are demanded not only in the context of obligatory worship such as prayer, fasting, almsgiving, etc., but also all activities that are of good value in their lives are carried out with the aim of approaching themselves to their creators. Both as a mu’abbid, as well as a caliph are required to reflect the attributes of God into him and make those qualities actual in various actions. The pursuit of the attributes of God is a necessity in the formation of humanity of Muslim human beings as a portrait and symbol of goodness and virtue that must always be imitated and strived to be a later attitude towards self-actualization. Humans have the duty to organize the world in such a way that it can make people live in prosperity, peace, security and happiness.